Ingegna Romana. From Sources to Models, from Artefacts to Reconstructions (diségno, 2024)
We present an aspect of the research activity shared with the students who approached the topic: Comparative Analyses and Certified Reconstructions for a correct experimental archaeology of Roman artillery. The occasion seemed useful to reflect on the tangibility of models in which to break down, in the light of current technologies, the configurations between material and immaterial values. For this purpose, we present surveys of physical reconstructed prototypes of catapults from the imperial republican era, based on three types of sources and tested in operation. Moving from the interpretation of the photogrammetric acquisitions to the numerical control of the models based on reality, we look at the dialectical tension between opposing past and present paradigms: survey/design, analogue/digital, tangible/intangible. The transversal aspects of the phenomena related to ontologies that characterize the commensuration of components and building systems, i.e. material, cultural and thus historical, stand out as multidimensional vectors potentially capable of directing cultural policies. Advanced visualizations, based on the rewriting of ancient obsidian histories, promise in the case study to become flywheels for the redevelopment of archaeological areas even of considerable renown.
Keywords: Roman artillery; digital culture; physical model; virtual model